A preliminary survey on mode choice and its effect in users' satisfaction on their journey to the railway station - Nur Fahriza, Mohd Ali; Ahmad Farhan, Mohd Sadullah; A., Zulkiple (Institute of Physics Publishing, 2018)
This paper focuses on two lines of investigation with regard to mode choice to Klang Komuter Station. Firstly, the profile of the access modes on journeys to the railway station is analysed. Secondly, the relationship of users' mode choice towards overall perception on traveling from home to the railway station is estimated. The data collection was conducted via Revealed Preferences / Stated Preferences (RP/SP) Survey. Meanwhile, the analysis that was implemented in this study was correspondence analysis. This paper discussed more on journey purposes and the effects of distances from home to the railway, users' trip purposes and travel time between car and bus that was found to have an important effect on the users' mode choice and their satisfaction on their journey to the railway station. The results show that users were more satisfied to reach the station by car instead of the bus.